Bipolar-barrier tunnel heterostructures for high-sensitivity mid-wave infrared photodetection - Fakun Wang; Song Zhu; Wenduo Chen; Ruihuan Duan; Tengfei Dai; Hui Ma; Congliao Yan; Shi Fang; Jianbo Yu; Yue Zhang; Qikan Dong; Wenjie Deng; et al. (Light: Science & Applications)
Abstract The rapid development of modern infrared optoelectronic technology has driven a growing demand for high-sensitivity mid-wave infrared (MWIR) photodetectors capable of reliable room-temperature operation. Achieving optimal specific detectivity, a critical performance metric for MWIR photodetection, remains challenging due to inherent limitations imposed such as high dark current, low optical absorption, or both. To address these challenges, we present an approach based on a bipolar-barrier architecture featuring a black phosphorus (BP)/MoTe2/BP tunnel heterostructure integrated with an Au reflector. This configuration delivers simultaneous electrical and optical enhancement, effectively suppressing dark currents and significantly increasing optical absorption. The bipolar-barrier structure minimizes dark current by blocking thermally excited and bias-induced carrier leakage, while facilitating efficient tunneling of photogenerated carriers via trap-assisted photogating mechanisms. In addition, the Au reflector enhances optical absorption through interference effects. As a result, the heterostructure achieves remarkable performance metrics, including a room-temperature specific detectivity of ∼3.0 × 1010 cm Hz0.5 W−1, a high responsivity of ∼4 A W−1, and an external quantum efficiency of ∼140% within the MWIR range. These results establish the bipolar-barrier tunnel heterostructure as a highly efficient platform, paving the way for the next generation of advanced infrared optoelectronic devices.